Pengaplikasian Matlab dan Audacity Sebagai Pendeteksi Bunyi Kerusakan Pada Pompa Rotary Tipe GD 123 MC - Fachriza, Andrian; Lesmana, I Gede Eka; Bunga, Nely Tobing (Proceeding Mercu Buana Conference on Industrial Engineering, 2020)
In the environment and people's lives, noise is very influential, especially human voice. And it can also be in the form of vehicles, operating machines, industrial equipment, and so on. As the progress of Science and Technology (IPTEK) is very rapid we can use the noise to find out the state of a machining system that is operating. In a sound must have a different frequency range, from the comparison of these frequencies can be known the state of a system. The application used in determining the frequency range is Matlab and Audacity by entering a code about the frequency range. The results of the comparison of frequency ranges are graphs. The machining system used is a rotary pump type GD 123 MC in data collection used several conditions, namely normal conditions, clogged inlet pipes, and cavitation. From the results of data processing, a graph of frequency ranges can be generated, from the graph it can be used as a reference of the conditions possessed by such a machining system. The graph is also used as an initial database to detect the condition of an engine or even detect a failure in a machining system. The results of the above patterns can make it easier to check the condition of a machinery system preventively.